2011
DOI: 10.3174/ajnr.a2817
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Pain in Patients with Conservatively Treated Osteoporotic Vertebral Compression Fractures: Results from VERTOS II

Abstract: BACKGROUND AND PURPOSE:We analyzed the natural course of conservatively treated osteoporotic vertebral compression fractures from VERTOS II, a randomized trial of vertebroplasty and conservative therapy in 202 patients with vertebral compression fractures. We assessed the proportion of patients who developed chronic back pain and possible risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 11 publications
1
58
0
Order By: Relevance
“…However, important functional limitation and pain persist during the first year in approximately one-third of patients, and in such situations, additional treatment is needed. 3 These patients who are refractory to conservative management may benefit from percutaneous surgical techniques developed over the last 20 years, such as vertebroplasty (VP) 4 and kyphoplasty (KP), which aim to lessen the pain, stabilize the fracture, reduce the pulmonary complications, and improve patients' quality of life. 5 These percutaneous techniques have now become the most widely used treatment option and have displaced open surgery, owing to their lesser invasiveness, fewer complications, and efficacy in reducing the morbidity and mortality associated with VFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, important functional limitation and pain persist during the first year in approximately one-third of patients, and in such situations, additional treatment is needed. 3 These patients who are refractory to conservative management may benefit from percutaneous surgical techniques developed over the last 20 years, such as vertebroplasty (VP) 4 and kyphoplasty (KP), which aim to lessen the pain, stabilize the fracture, reduce the pulmonary complications, and improve patients' quality of life. 5 These percutaneous techniques have now become the most widely used treatment option and have displaced open surgery, owing to their lesser invasiveness, fewer complications, and efficacy in reducing the morbidity and mortality associated with VFs.…”
Section: Introductionmentioning
confidence: 99%
“…VP is an imaging-guided minimally invasive technique in which cement is injected into the fractured vertebral body (Figures 2,3,and 4) to lessen the pain and stabilize the fracture, without restoring vertebral height. KP is a similar technique, but it differs from VP in that a balloon is inserted into the vertebral body and is insufflated to reduce the fracture-restoring vertebral height and creating a cavity into which cement is then injected 6 (Figures 5-7).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, multiple treatment modalities have been indicated including pain medication, medical osteoporosis treatment, physical therapy, bracing, and surgery. The surgical indications for vertebral augmentation procedures, such as kyphoplasty and vertebroplasty, have varied in the literature, but are most commonly reserved for fractures with significant local deformity and patients with pain refractory to conservative management (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…After hospitalization, Ͼ50% require ongoing care 4 ; chronic pain occurs in 40%. 9 Thus, while medical management is widely used, there are significant negative effects. In patients with severe pain, vertebral augmentation (vertebroplasty and/or kyphoplasty) may be considered.…”
mentioning
confidence: 99%
“…Further post hoc analysis of the medical cohort revealed that 60% achieved sufficient (VAS Յ 3) pain relief by 12 months, with most within 3 months. 9 There were no predictors to identify the 40% who developed chronic pain. This finding led the investigators to postulate that vertebroplasty may be justified for patients without sufficient pain relief after 3 months of medical management, setting the stage for further trials.…”
mentioning
confidence: 99%